KOMITMEN TUJUAN ANGGARAN DAN DAMPAK INFORMASI KINERJA ANGGARAN: SUATU PENDEKATAN PERMODELAN PERSAMAAN STRUKTURAL - ., SELLY (: 2303-1719)
This paper examines budget goal commitment and informational effects of budget participation on performance. A structural model is proposed and tested that includes budget participation, budget goal commitment, job-relevant information, and job perfomance variables. Based on theory, budget participation will give positive influence to subordinate’s commitment for budget and in the end will improve their performance. The data were collected by survey questionnaires. Two hundred middle-level managers were chosen randomly from manufacturing companies in Indonesia, and 126 middle-level managers participated in the project. A structural equation modeling technique was used to test hypothesized linkages. The structural equation modeling technique that used in this paper is multivariate technique SEM and assisted by AMOS 18.0 program. As the result, positive and significant influence was found for the effects of budget goal commitment and informational roles of budget participation on job performance.